2021
DOI: 10.3389/fsufs.2021.711284
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Arrangement and Biofertilizers Enhance the Performance of Legume—Millet Intercropping System in Rainfed Areas of Southern India

Abstract: Intercropping is a well-established practice to enhance the yield in low-input agriculture, and beneficial microbes such as arbuscular mycorrhizal fungi (AMF) combined with plant growth promoting rhizobacteria are being used as an effective and sustainable measure to improve yields. In this study, we tested if biofertilizers can not only enhance the yield of crops in monoculture as has previously been demonstrated but can also enhance the yield of intercropping systems. We hypothesized that because AMF can for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Therefore, an ecological solution was required, such as bio-fertilizers, which could be successfully used to increase the absorption and accumulation of important nutrients in edible parts of plants, thereby supporting high yields and nutrient density in crops in a sustainable way ( 60 , 61 ). A lot of studies have examined the impact of bio-fertilizers on soybean–cereals, as well as millet–legume intercropping, with variable results ( 42 , 62 , 63 ), but research on common millet and soybean intercropping was not published yet. Therefore, this study showed for the first time results from field trials of common millet–soybean intercropping in combination with BF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an ecological solution was required, such as bio-fertilizers, which could be successfully used to increase the absorption and accumulation of important nutrients in edible parts of plants, thereby supporting high yields and nutrient density in crops in a sustainable way ( 60 , 61 ). A lot of studies have examined the impact of bio-fertilizers on soybean–cereals, as well as millet–legume intercropping, with variable results ( 42 , 62 , 63 ), but research on common millet and soybean intercropping was not published yet. Therefore, this study showed for the first time results from field trials of common millet–soybean intercropping in combination with BF.…”
Section: Discussionmentioning
confidence: 99%